2020
DOI: 10.1002/cncr.33307
|View full text |Cite
|
Sign up to set email alerts
|

Indoor tanning exposure in association with multiple primary melanoma

Abstract: Background Patients with primary cutaneous melanoma are at increased risk for subsequent new primary melanomas. Indoor tanning is a recognized risk factor for melanoma. This study was aimed at determining the association between indoor tanning and the occurrence of multiple primary melanoma. Methods This was a retrospective case‐control study of cases with multiple primary melanoma and sex‐matched controls with single primary melanoma retrieved at a 1:2 ratio from the Biological Sample and Nevus Bank of the Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…We performed age‐, sex‐, and stage‐matched studies within the biospecimen repository of this institution. These factors are important to account for because we previously reported that patients with MPMs were younger at time of diagnosis of first primary melanoma, and more likely to be diagnosed at stage 0 or 1 3 . Our MPM cohort also shows female predominance, whereas melanoma has been classically viewed as a male‐biased disease 15 .…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…We performed age‐, sex‐, and stage‐matched studies within the biospecimen repository of this institution. These factors are important to account for because we previously reported that patients with MPMs were younger at time of diagnosis of first primary melanoma, and more likely to be diagnosed at stage 0 or 1 3 . Our MPM cohort also shows female predominance, whereas melanoma has been classically viewed as a male‐biased disease 15 .…”
Section: Discussionmentioning
confidence: 80%
“…These factors are important to account for because we previously reported that patients MPMs were younger at time of diagnosis of first primary melanoma, and more likely to be diagnosed at stage 0 or 1. 3 Our MPM cohort also shows female predominance, whereas melanoma has been classically viewed as a male-biased disease. 15 The major limitations included the number of samples reporting TILs and with PBMCs available for transcriptional profiling, although these results were exploratory in nature.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Tanning bed usage and the initiation of tanning behavior at a younger age have both been implicated in incidences of melanoma at a significantly younger age [ 42 , 43 ]. Beyond the risk of developing an initial melanoma, indoor tanning practices are significantly associated with the development of multiple primary melanomas [ 44 ]. Given the increased risk of melanoma in the context of tanning behavior, tanning is not a recommended practice for either vitamin D supplementation or for cosmetic reasons.…”
Section: Sun-seeking Behaviors and Melanoma Developmentmentioning
confidence: 99%